Analyzing the Economic Impact of Trademark Applications by Korean Companies - Hyukjoon Kim; Hyun Kwak (Journal of Intellectual Property)
This study examined the economic effects of trademark applications by domestic companies on production and employment growth. To conduct the analysis, panel regression analysis was applied using the Corporate Activity Survey data from 2006 to 2018. The results confirmed that trademark applications have a positive effect on the increase in production and employment of companies. Particularly, it was found that trademarks also have a positive moderating effect on the impact of R&D expenditure and patents on production and employment. This indicates that when companies engage in trademark application activities in addition to technological development activities such as R&D and patent applications, a synergy effect on economic outcomes can be generated. These results provide important implications for companies to strategically utilize trademark applications to increase productivity and employment.